Developing Supra-European Emissions Trading Schemes: An Efficiency and International Trade Analysis - Victoria Alexeeva-Talebi; Niels Anger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Given the coexistent EU priorities concerning the competitiveness of European industries and international emissions regulation at the company level, this paper assesses the efficiency and competitiveness implications of linking the EU Emissions Trading Scheme (ETS) to emerging trading schemes outside Europe. Currently, countries like Canada, Japan or Australia are contemplating the set up of domestic ETS with the intention of linking up to the European scheme. While a stylized partial-market analysis suggests that the integration of trading systems is always beneficial in efficiency terms, our applied general equilibrium approach shows that the aggregate welfare impacts of linking the EU ETS are rather limited. We further find that the trade-based competitiveness effects of linking the European ETS crucially depend on the linked trading system: Although EU economy-wide competitiveness varies only moderately across linking scenarios, the sectoral decomposition of these aggregate effects shows that European industries are much more sensitive to the linking constellation. Similarly, the incentives for non-EU regions to join the European system display considerable heterogeneity. A stricter allowance allocation within domestic ETS can, however, substantially improve the overall prospects for establishing supra-European emissions trading schemes.
Keywords: D58; Q48; H22; H21; 330; Emissions Trading; EU ETS; Linking; Competitiveness; CGE model